Search for a heavy composite Majorana neutrino in the final state with two leptons and two quarks at root s=13 TeV - (:unkn) unknown (ELSEVIER, 2017)
A search for physics beyond the standard model in the final state with two same-flavour leptons (electrons or muons) and two quarks produced in proton-proton collisions at root s = 13 TeVis presented. The data were recorded by the CMS experiment at the CERN LHC and correspond to an integrated luminosity of 2.3 fb(-1). The observed data are in good agreement with the standard model background prediction. The results of the measurement are interpreted in the framework of a recently proposed model in which a heavy Majorana neutrino, N-l, stems from a composite-fermion scenario. Exclusion limits are set for the first time on the mass of the heavy composite Majorana neutrino, m(Nl), and the compositeness scale Lambda. For the case m(Nl) = Lambda, the existence of N-e (N-mu) is excluded for masses up to 4.60 (4.70) TeV at 95% confidence level. (C) 2017 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Exotica; COLLISIONS; MODELS